2009
DOI: 10.1016/j.colsurfa.2009.02.015
|View full text |Cite
|
Sign up to set email alerts
|

The CMC-like behaviour of bile salts as probed by photoexcited Rose Bengal

Abstract: The onset of the aggregation process in aqueous bile salt (BS) solutions remains a debated question. This study aimed at investigating this point through the detection of BS monomers and small aggregates using the dye Rose Bengal. Results showed that a few small BS aggregates led to a red shift of the absorption spectrum, while the BS monomer reacted with the photo-induced semi-oxidized dye and decreased its decay rate constant. The dye was dissolved in aqueous solution (10 mmol dm -3 NaOH) of sodium cholate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Aggregation of bile salts is responsible for their important physiological functions; for example, they often act as an emulsifier or solubilizing agents for hydrophobic dietary lipids in the intestine or as gallstone solubilizing agents in clinical medicine [4][5][6][7]. Therefore, different aspects of the aggregation process of bile salts in aqueous medium form a major topic of investigation by using various experimental [8][9][10][11][12][13] and computational techniques [14][15][16]. Apart from bile salts, phospholipids another important class of bio-surfactants (L-a-dimyristoylphosphatidycholine (DMPC), L-a-dipalmitoylphosphatidycholine (DPPC), and L-a-dilauroylphosphatidylethanolamine) have also been explored in mixed monomeric and dimeric cationic surfactant solutions [17,18] with the help of surface tension and fluorescence quenching measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation of bile salts is responsible for their important physiological functions; for example, they often act as an emulsifier or solubilizing agents for hydrophobic dietary lipids in the intestine or as gallstone solubilizing agents in clinical medicine [4][5][6][7]. Therefore, different aspects of the aggregation process of bile salts in aqueous medium form a major topic of investigation by using various experimental [8][9][10][11][12][13] and computational techniques [14][15][16]. Apart from bile salts, phospholipids another important class of bio-surfactants (L-a-dimyristoylphosphatidycholine (DMPC), L-a-dipalmitoylphosphatidycholine (DPPC), and L-a-dilauroylphosphatidylethanolamine) have also been explored in mixed monomeric and dimeric cationic surfactant solutions [17,18] with the help of surface tension and fluorescence quenching measurements.…”
Section: Introductionmentioning
confidence: 99%
“…20−25 It seems that aggregation of bile salt derivatives proceeds stepwise over a broad concentration range and with a great portion of polydispersity. It is why Seret and Bahri 24 suggested that, instead of critical micelle concentration, cmc, usually used to describe the micellization process, the concept of micellar dissociation concentration, defined as a concentration below which any dilution leads to disruption of the aggregates, should be applied. The efficiency of protein stabilization is highly related to the surfactant concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Their respective structures include a polar hydrophilic surface, a nonpolar hydrophobic surface, and a short hydrophilic tail. 17 BSs are natural anionic surfactants that can self-assemble in aqueous media to form supramolecular structures such as micelles, 18 hydrogels, 19 and liquid crystals. 20 Among them, the hydrogels based on sodium lithocholate or deoxycholate (NaDC) can be formed under appropriate pH conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Their respective structures include a polar hydrophilic surface, a nonpolar hydrophobic surface, and a short hydrophilic tail . BSs are natural anionic surfactants that can self-assemble in aqueous media to form supramolecular structures such as micelles, hydrogels, and liquid crystals . Among them, the hydrogels based on sodium lithocholate or deoxycholate (NaDC) can be formed under appropriate pH conditions. ,, Adding metal ions to BS systems, however, can improve gel performance because the introduced metal ions not only triggers the self-assembly process but also imparts unique properties to gels such as conductivity and luminescence .…”
Section: Introductionmentioning
confidence: 99%